Enhanced photodynamic leishmanicidal activity of hydrophobic zinc phthalocyanine within archaeolipids containing liposomes - Pérez, A. P. (2014)
Fil: Pérez, A. P. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología. Programa de Nanomedicinas; Argentina